Feldspar-Modified Methacrylic Composite for Fabrication of Prosthetic Teeth - Raszewski, Zbigniew; Kulbacka, Julita; Pakuła, Daria; Brząkalski, Dariusz; Przekop, Robert E (Materials (Basel, Switzerland), 2023)
This study was aimed at investigating poly(methyl methacrylate) (PMMA), modified with a silanized feldspar filler at 10 wt.% and 30 wt.%, as a dental material system for the production of prosthetic teeth. Samples of this composite were subjected to a compressive strength test, three-layer methacrylic teeth were fabricated with the said materials, and their connection to a denture plate was examined. The biocompatibility of the materials was assessed via cytotoxicity tests on human gingival fibroblasts (HGFs) and Chinese hamster ovarian cells (CHO-K1). The addition of feldspar significantly improved the material's compressive strength, with neat PMMA reaching 107 MPa, and the addition of 30% feldspar raising it up to 159 MPa. As observed, composite teeth (cervical part made of neat PMMA, dentin with 10 wt.%, and enamel with 30 wt.% of feldspar) had good adhesion to the denture plate. Neither of the tested materials revealed any cytotoxic effects. In the case of hamster fibroblasts, increased cell viability was observed, with only morphological changes being noticed. Samples containing 10% or 30% of inorganic filler were determined to be safe for treated cells. The use of silanized feldspar to fabricate composite teeth increased their hardness, which is of significant clinical importance for the duration of use of non-retained dentures.
Keywords: feldspar silane; biomaterials; methacrylic polymer; surface modification; compressive strength; connection between teeth and denture base; cytotoxicity; acrylic teeth